Reply to Hsiao - Barrigar, Chris (The Evangelical quarterly, 2024)
Barrigar addresses more directly the distinction between Hsiao’s individualist-level priority on self-protection and the author’s priority on the well-being (security) of society as a whole (and thereby of the individuals within society). The author argues that our starting point as Christians is not natural law and individual rights but rather God’s vision of shalom for societies. (On top of which the author argues that Hsiao’s natural law claims are disputable anyway). The author also addresses more substantially the issue of collateral harms to society within high gun-culture, a significant type of cost to society that is inadequately recognised in the literature. The author concludes by returning to his central argument, namely, that a central component of any theology of guns must include an account of agape-love, of self-sacrifice for the benefit of others, which Hsiao’s response insufficiently addresses.